Investigation of the Activity of AIPO4 and Al2(HPO4) as Support for Pt in the Hydrogenation of o-Xylene with Comparison to Pt/Al2O3 - M. Asfour, Hasan; Saymeh, A.; Arafa, Isam (Asian Journal of Chemistry, 2010)
The active forms of AlPO4 and AI2(HPO4)3 supported platinumhave less activity than alumina supported platinum for thehydrogenation of o-xylene in the temperature range 30-250oC. Thischange is attributed to the strong metal support interaction. Theactivity of PtAI2(HPO4)3 is exhibited after calcination at 530°C,while the activity of Pt/AlPO4 is exhibited before calcination. TheIR and thennal analysis of these two support, before and aftercalcination at 530oC, show some changes in their crystal forms.